Study of magnetic structures of an arch filament system in the photosphere and chromosphere - Tardelli Ronan Coelho Stekel (2018)
In the last years, advances in solar observation provided by large improvements in the spatial, spectral and temporal resolution, have permitted the ground-based observatories to overcome the atmospheric seeing effect and obtain diffraction limited observations. Taking advantage of this new scenario of solar observations, we present an investigation of the magnetic structures of an arch filament system by using the Stokes profiles of the Si i 10827 Å line and He i 10830 Å triplet. The Stokes profiles are observed with GRIS spectrograph installed at the 1.5 m GREGOR telescope. We observed an emerging flux region over the NOAA AR 12252, with flux tubes emerging through the photosphere into the chromosphere. In the chromosphere it is identified as an arch filament system, with dark filaments, crossing the polarity inversion line, and connecting the footpoints of opposite polarity. The Doppler analysis of the He i 10830 Å triplet presents supersonic downflows of more than 40 kms−1 at the footpoints. The supersonic velocities are observed employing two different components for the He i, that presents subsonic and supersonic downflows in the same resolution element. The downflows result from the upward motions of new emerging flux tubes, that lead the photospheric material to higher layers close to the center of the filament. The upflows reach more than 1 kms−1 in the filament center. Then, the material flows down from the upper chromosphere to the photosphere, along with the field lines, reaching the chromospheric footpoint with supersonic velocities. The inversion of full-Stokes is performed with the HeLix+ code for both photosphere and upper chromosphere. We analyze the properties of the atmospheric parameters retrieved from the spectropolarimetric observation and provide a description of the magnetic structure of the emerging flux region and arch filament system. The magnetic structure are analyzed by using the azimuth ambiguity correction, polarity inversion line determination, magnetic loops reconstruction and linear force-free extrapolation.